Pseudoplectania mystica (Ascomycota, Pezizales), a new cup fungus with an endophytic habit of a broad range of host plants - Lin, Jia Y.; Guo, Ling-Han; Li, Guang-Mei; Zhang, Ming; Xie, De-Chun; He, Shu-Xian; Yang, Kun L. (Phytotaxa, 2024)
A cup fungus producing ascomata on senescing to dead rhizomes of bamboo in East China is described as Pseudoplectania mystica sp. nov. (Ascomycota, Pezizales) based on morphological, ecological and phylogenetic evidence. Some sequences of unidentified endophytic fungi uploaded to the GenBank database by other researchers were also identified as P. mystica in our phylogeny. By checking the original literature of these sequences, P. mystica was further found to act as an endophyte in a broad range of host plants including Aegiceras, Cinnamomum, Dendrobium and Lindera, probably lurking in the tissues of the host plants as invisible mycelium in most cases and only producing visible ascomata following senescence of the host tissues. Such ecology and a combination of all its morphological characteristics make P. mystica recognizable from other known species of Pseudoplectania. This study contributes to the understanding of the species diversity and lifecycle of Pseudoplectania.